Dispersion variation in ring-type erbium-doped fiber ultrashort pulse laser with single-wall carbon nanotube-based tapered fiber saturable absorber - Mohamad, Hafizah; Abu Bakar, Muhammad Hafiz; Mahdi, Mohd Adzir (Wiley Periodicals, 2015)
Dispersion effect on mode-locked ring-type erbium-doped fiber laser was experimentally observed. Cutback method was used on the cavity length to vary the dispersion. Stable pulse trains with 9.27-MHz frequency at optimum pulse duration of 864 fs were achieved when the cavity was composed of 17-m single-mode fiber with 5-m gain medium.